LASER ACUPUNCTURE AS A NON-INVASIVE STRATEGY TO OPTIMIZE RABBIT GROWTH: HISTOMORPHOMETRIC AND LEUCOCYTE ANALYSIS STUDY - Ritonga, Mudhita Zikkrullah; Hasan, Denny Irmawati; Hidanah, Sri; Lokapirnasari, Widya Paramita (Universitas Syiah Kuala, 2024)
This study evaluates the effects of laser acupuncture on jejunum morphometry and the differential leucocyte responses in rabbits. Twenty-four Hycole rabbits, aged four to twelve weeks with an average weight of 1046 g, were administered laser acupuncture once a week for six weeks. The rabbits were housed in individual cages and randomly divided into three groups. Group 1 (control) received inactive laser acupuncture for predetermined acupuncture points (Bladder 13, Bladder 15, and Bladder 21). Group 2 received active laser acupuncture at the exact points BL 13, BL 15, and BL 21, using a laser dose of 0.2 Joules. Group 3 received laser acupuncture near, but not precisely at, these exact points. Blood samples were collected at the end of the 12th week, and the jejunum was excised for histomorphometric analysis. The results indicated that rabbits in group 2 had significant increases (P0.05) in villus height (VH), and villus width (VW) compared to groups 1 and 3. The results of differential leucocytes measurements in groups 1, 2, and 3 were lymphocytes 64.2037%, 61.80.374%, 61.80.489% (normal: 30-85%); monocytes 130.447%, 12.20.374%, and 13.40.244% (normal: 4-13.4%), granulocytes 23.40.748%, 260.447%, and 24.80.374 (normal: 21-73%), respectively. These findings indicate that laser acupuncture targeted at BL13, BL15, and BL21 points promotes villi development and maintains differential leukocyte parameters within the normal range.